Optimum utilization of coconut flour in ginger gem and noodles - Yap, Diana Echavez; Guzman, Matilde P. (1972.)
ABSTRACT The study was undertaken to explore the possibility of substituting a judicious amount of coconut lour in ginger gems and noodles without reducing the acceptability of the products. In the ginger gems, 10, 20, 30 and 40 per cent coconut flour were incorporated into the basic recipe for ginger cookies. A similar procedure was followed for the noodles except that the levels of substitution used were 10, 20 and 30 per cent. Control samples made from 100 per cent wheat flour were used as reference standards in the sensory evaluation of the products. The results of the study indicated that the optimum level of substitution of coconut flour in ginger gems without adversely affecting the flavor of the products, is 20 per cent, while for the coconut noodles, the optimum level of substitution with coconut flour is 15 per cent.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut flour